P 20. Stimulus-dependent behavioural disorder in patients with ANT-DBS for Epilepsy. Issue 8 (August 2021) - Kukhlenko, R.; Frantsev, R.; Buentjen, L.; Voges, J.; Kukhlenko, O.; Haghikia, A.; Frodl, T.; Schmitt, F.
Abstract : Deep brain stimulation (DBS) targeting the anterior nucleus of the thalamus (ANT) is as an effective and safe treatment option for patients with resistant epilepsy. A SANTE Study reported that there was a gradual improvement in selected neuropsychological test results in patient with DBS in ANT. Among those improvements there were reported a number of psychiatric adverse affects. However little is studied about immediate neuropsychological effects of DBS in ANT. Recently demonstrated Voges B. et. al (2015) a stimulus- and voltage-dependent effect interrupting sleep and leading to the occurrence of neuropsychiatric symptoms (npS) (e.g. depression, mood instability, disturbed sleep) during ATN-DBS. We here present one patient with a voltage-independent developing of npS during ANT-DBS. The 45-year-old right-handed female patient with mental retardation with autistic spectrum disorder presented with focal not lesional refractory epilepsy. The average seizure frequency was 6.1 per day with a range of 1 to 16 seizures daily. After failure of 13 AED"s, a DBS-ANT was initiated at the age of 44. Follow up simultaneous EEG- video recording from 26 surface electrode contacts after beginning to stimulate with standard parameters (unipolar cyclic (1min ON/5min OFF) stimulation with 5 V stimulation amplitude, 120 Hz stimulation frequency and a pulse width of 90 μs) there were seen a directly dependence of neuropsychiatric symptoms (stereotypical movements with sitting down, torso wiggling (Body rocking) with or without singing) and impulse onset. In video-EEG monitoring we determined, that the duration of npS was also the same as impulse lasts. A clinical response to stimulation was 84 %. We improve adverse effects changing the programming settings: the amplitude was gradually reduced to two volts, the stimulation frequency 120 Hz and a pulse width of 90 μs where the same. Actual case report devoted to immediate complex behavioural disorder, which does not fulfil criteria for a complex focal seizure, and is strongly associated with unipolar bilateral stimulation of ANT. The actual clinical presentation of the DBS induced behavioural disorder semiologically coincide with the term "stereotypic movement disorder". We hypothesize that impaired function of ARAS lead to reduced behavioural suppression of impulse mediated behaviour in the patient with mental retardation. We analysed her video-EEG before she was being stimulated and noticed, that she already had a typical body movement (body rocking) but much less frequently. Obviously a DBS of ANT had had a strong influence on behavioural disorder of our patient and was reversible after adjusting the stimulation parameters.